0
$\begingroup$

Given an arithmetic progression where the $$ p\text{-th term}=2p+4q-5r\\ q\text{-th term}=3p+3q-5r\\ r\text{-th term}=3p+4q-6r$$ determine the value of the $(p+q+r)$-th term.

Also, find $n$ where the $n$-th term equals zero.

__
NB: This question was designed as an extension of some similar questions here on MSE.

$\endgroup$
1
$\begingroup$

We have $$a_p = a_1 + (p-1)d = 2p+4q-5r...(1)$$ $$a_q = a_1 + (q-1)d = 3p+3q-5r...(2)$$ $$a_r =a_1 + (r-1)d = 3p+4q-6r...(3)$$ Now, subtracting $(1)$ and $(2)$ gives us $d=-1$ and thus $a_1 = 3p+4q-5r-1$.

Then, $$a_{p+q+r} = a_1 + (p+q+r-1)d = 3p+4q-5r-1 -p-q-r+1 = 2p+3q-6r$$ If $a_n = 0$, then $$a_1 + (n-1)d = 0 \Rightarrow n = a_1 + 1=(3p+4q-5r)^{\text{th}} \text{ term }$$

$\endgroup$
  • $\begingroup$ Thanks for your solution. Minor typo in answer to $a_{p+q+r}$. $\endgroup$ – hypergeometric Dec 30 '16 at 15:15
  • $\begingroup$ Yes, @hypergeometric It is corrected. $\endgroup$ – Rohan Dec 30 '16 at 15:16
1
$\begingroup$

Let $a_i$ be the $i$-th term for $i\in\mathbb{N}$. Then observe that, $$a_{p+q+r}=a_1+(p+q+r-1)$$$$a_{p}=a_1+(p-1)$$$$a_{q}=a_1+(q-1)$$$$a_{r}=a_1+(r-1)$$Now observe that \begin{align}a_p+a_q+a_r&=3a_1+(p+q+r-3)\\&=3a_1+3(p+q+r-3)-2(p+q+r-3)\\&=3a_1+3(p+q+r-1)-6-2p-2q-2r+6\\&=3a_{p+q+r}-2(p+q+r)\end{align}Consequently, $$\boxed{a_{p+q+r}=\dfrac{a_p+a_q+a_r+2(p+q+r)}{3}}$$


You can, use the above argument to prove a more general problem. Namely,

Given an arithmetic progression of $n$-terms (the $i$-th term being denoted as ${\bf{T}}(i)$ with $i\in\mathbb{N}$ if $p_1,p_2,\ldots,p_m$-th terms are known (where $m,p_1,p_2,\ldots,p_m\in\mathbb{N}$ and $m\le n$) then what is ${\bf{T}}\left(\displaystyle\sum_{i=1}^n p_i\right)$?

Hint: Prove that, $$\boxed{\displaystyle\sum_{i=1}^m {\bf{T}}(p_i)=m{\bf{T}}\left(\displaystyle\sum_{i=1}^mp_i\right)-(m-1)\left(\displaystyle\sum_{i=1}^m p_i\right)}$$

$\endgroup$
0
$\begingroup$

Note that adding $p,q,r$ back to the $p,q,r$-th terms respectively gives a constant $3p+4q-5r$.

Hence the $n$-th term of the AP is given by

$$U_n=3p+4q-5r-n$$

Putting $n=p+q+r$: $$\color{red}{U_{p+q+r}=2p+3q-6r}$$

From the definition of $U_n$ it is clear that for $U_n=0$, $$\color{red}{n=3p+4q-5r}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.